Got water? Social divisions and access to public goods in rural India - Divya Balasubramaniam; Santanu Chatterjee; David B. Mustard (Institute for the Study of Labor (IZA), 2011)
We use data for 436 rural districts from the 2001 Census of India to examine whether different aspects of social divisions help explain the wide variation in access to tap water across rural India. Studies linking social fragmentation to public goods usually aggregate different types of fragmentation into one index. In contrast, we use disaggregated measures of social fragmentation to show that different types of social fragmentation are associated with dramatically different outcomes for access to tap water in rural India. Communities that are heterogeneous in terms of caste (within the majority Hindu religion) have lower access to tap water than correspondingly homogeneous communities. Communities that are fragmented across religions have higher access to tap water than correspondingly homogeneous communities. This underscores the importance of heterogeneity both within and across religions. Therefore, relying on aggregate measures of social fragmentation may conceal different effects of the component measures and obscure important information regarding the design of policies related to public goods.
urn:nbn:de:101:1-201110102341
Keywords: H4; O2; 330; public goods; social fragmentation; water; public policy; India; Wasserversorgung; Lokales öffentliches Gut; Soziale Schicht; Ländlicher Raum; Indien